Electric double-layer capacitors with tea waste derived activated carbon electrodes and plastic crystal based flexible gel polymer electrolytes - Suleman M.; Deraman M.; Othman M.A.R.; Omar R.; Hashim M.A.; Basri N.H.; Nor N.S.M.; Dolah B.N.M.; Hanappi M.F.Y.M.; Hamdan E.; Sazali N.E.S.; Tajuddin N.S.M.; et al. (Institute of Physics Publishing, 2024)
Indexed by WOS/Scopus